ANALYSIS OF LEARNING ACCOUNTING WITH ADDIE MODEL IMPROVING LEARNING QUALITY - Zurika, Henny (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This study aim to improve the quality of accounting learning more effectively through the ADDIE model as one model of learning system design that shows the basic stages of the learning system is simple and easy to learn with the stages of Analysis,Design,Development,Implementation,Evaluation.